Crisis Communication and the Norwegian Authorities: 22 July and the Chernobyl Disaster: Two Catastrophes, Dissimilar Outcomes - Vettenranta, Soilikki (Nordicom review, 2015)
The present article examines how crisis communication after catastrophes can strengthen society or undermine trust, credibility and confidence between the authorities and the general public. The two cases examined are the Norwegian authorities’ communicative response to the Chernobyl power plant disaster on 26 April, 1986, and the terrorist attacks on the government complex in Oslo and the Labour Party youth camp on the island of Utøya on 22 July, 2011. The analysis compares the initial phase of crisis communication. A serious communication crisis arose between the authorities and the public after Chernobyl, while communication during the early days after 22 July was successful. The difference is explained by the concept of rationality; crisis communication after Chernobyl was based on technical rationality, whereas communication after the terror attacks was grounded on the rationality of caring. The theoretical framework originates from Heidegger’s existential phenomenology with special focus on the existentiales Being-in-the-World, State of Mind and Care.